(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: To describe knowledge and practice of infectious disease surveillance (IDS) among health workers at district and commune levels in Vinh Thanh district, Binh Dinh province, in 2022. Methods: Cross-sectional study, quantitative interviews with 66 health workers by structured questionnaire, from January to October 2022 in Vinh Thanh district, Binh Dinh province. Results and conclusion: Research showed that 66.67% of health workers have a satisfactory general knowledge of IDS, the highest in data management and data collection (92.31%), and lowest in the knowledge of weekly reporting time (30.3%). Regarding IDS practice, 62.12% of health workers met the general requirements: good practice included IDS reporting (over 90%), data collection (over 85%), and weak practice included data analysis, risk assessment, pandemic situation identification and solution proposal (33.33%-60%).